Effect of universal adhesives on microtensile bond strength to hybrid ceramic - Mohamed M. Awad; Lamees Albedaiwi; Ahmed Almahdy; Rawaiz Khan; Nick Silikas; Muhanad M. Hatamleh; Fahad M. Alkhtani; Ali Alrahlah (BMC, 2019)
Abstract Background The aim of this study was to evaluate the effect of universal adhesives (UA) and silane on the microtensile bond strength (μTBS) of resin cement to a hybrid ceramic Vita Enamic (VE). Methods VE specimens were acid etched using hydrofluoric acid (HF) and were assigned to three groups (n = 10) based on the applied bonding technique. In group 1 (S), a silane-based primer was used as a surface treatment prior to the application of a resin cement (Variolink Esthetic DC). In group 2, a silane-containing UA, Clearfil Universal Bond (CUB) was used for the surface treatment, and in group 3, A silane-free UA, Tetric N-Bond Universal (TNU) was used for surface treatment. Resin cement build-ups were prepared. The bonded specimens were sectioned into resin-ceramic beams. Half of the beams of each group were stored for 24 h at 37 °C and the other half were subjected to a thermo-cycling aging. The microtensile bond strength (μTBS) was measured at a crosshead speed of 0.5 mm/min. Failure modes were assessed accordingly. Data were analyzed using a) two-way analysis of variance ANOVA followed by one-way ANOVA and Tukey tests between groups and b) independent t-test to detect differences (α = 0.05) for each group. The surface topographies of the ceramic surface were evaluated using scanning electron microscopy. Results The results showed that silane-based primer (S) application resulted in significantly higher (p < 0.05) μTBS values after 24 h and after thermocycling compared to both silane-containing UA (CUB) and silane-free UA (TNU). The μTBS values of all groups were significantly reduced after thermocycling. No statistically significant difference was observed between the μTBS of CUB and TNU after 24 h. However, TNU showed significantly higher μTBS after thermocycling. Different failure modes were observed, and adhesive failure was the most common in all groups. Marked surface topographic changes were observed following HF etching. Conclusion It is concluded that, the UAs tested cannot be recommended as substitutes to the silanization of Hybrid ceramic.